DAMPAK FINTECH TERHADAP INKLUSI KEUANGAN DI NEGARA BERKEMBANG - Selvia Dwi Oktaviany; Nurfadia, Dita (Yayasan Nuraini Ibrahim Mandiri, 2025)
This research comprehensively analyzes impact, Financial Technology (Fintech), financial inclusion, and developing (assuming developing countries or similar context countries through the methodology (Systematic Literature Review (SLR) method) and the guiding framework (guided by PRISMA), reviewing articles from 2020 to 2025. The research results indicate that fintech has become a transformative force in enhancing financial inclusion, especially in developing countries. The rapid development of fintech, driven by increased digital access, has facilitated easier and more affordable access to formal financial services for previously underserved communities. Various forms of fintech services such as e-wallets, digital payments, and online lending platforms (P2P lending) have proven effective in expanding the reach of financial services, empowering Micro, Small, and Medium Enterprises (MSMEs), and enhancing transaction efficiency. Although its contributions are significant, the effectiveness of fintech still faces challenges such as low financial literacy and uneven digital infrastructure, which can hinder full adoption. However, this research also emphasizes the crucial role of government policies and adaptive regulations in supporting the growth of a healthy fintech ecosystem, protecting consumers, and maintaining the stability of the financial system. Collaboration between regulators, industry players, and traditional financial institutions is necessary to Fintech can help build a financial system that includes everyone and lasts for the long term. It's not just a technological solution, but also a vital agent of social change in efforts to reduce inequality and enhance economic welfare in developing countries.